2019
DOI: 10.22190/fupes181017064p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Exercise Programs on Arterial Blood Pressure of the Elderly

Abstract: The value of arterial blood pressure is variable. It depends on the time of the day, external and internal factors such as genetics and lifestyle. Moderate and regular physical activity, as well as weight reduction, can affect the reduction of high arterial blood pressure (ABP). The influence of physical activity on the health of the elderly is not well researched. The objective of this systematic review study is to collect and analyze studies of the effects of different types of exercise programs on arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
5
0
4
Order By: Relevance
“…Destacam-se programas intervencionais específicos com idosos, como a melhoria da força dos MI e da capacidade respiratória com a caminhada, a força muscular dos MS e flexibilidade com a hidroginástica, e a força máxima geral com a prática de um programa de musculação [16][17][18] . No entanto, novos programas com exercícios funcionais vêm ganhando espaço para a prática entre os idosos, uma vez que seus benefícios também estão atrelados à saúde, à força 5 , ao equilíbrio e à agilidade 12 e por serem exercícios que simulem as AVD e AIVD do idoso 3 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Destacam-se programas intervencionais específicos com idosos, como a melhoria da força dos MI e da capacidade respiratória com a caminhada, a força muscular dos MS e flexibilidade com a hidroginástica, e a força máxima geral com a prática de um programa de musculação [16][17][18] . No entanto, novos programas com exercícios funcionais vêm ganhando espaço para a prática entre os idosos, uma vez que seus benefícios também estão atrelados à saúde, à força 5 , ao equilíbrio e à agilidade 12 e por serem exercícios que simulem as AVD e AIVD do idoso 3 .…”
Section: Discussionunclassified
“…Assim, exercícios que promovam a flexibilidade levam os idosos a realizar os movimentos de maneira mais segura, contribuindo para uma maior independência funcional e uma vida mais ativa 26 . Confirmando os achados nesta pesquisa (Tabela 2), os autores 16 de um estudo observaram que houve melhora significativa da flexibilidade de idosas após um programa intervencional de exercício físico e influência positiva para a melhora da qualidade de vida do grupo investigado, revelando a importância psicológica que o exercício físico também pode promover aos idosos.…”
Section: Discussionunclassified
“…[4] In particular, the positive in uence of physical activity on BP has been demonstrated by various epidemiological studies. [5][6][7] A metaanalysis of RCTs has shown that aerobic endurance training, dynamic resistance training and isometric training reduce resting systolic BP/diastolic BP by 3.5/2.5, 1.8/3.2 and by 10.9/6.2 mmHg, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[6] According to these studies, a combination of aerobic exercise and resistance training in older individuals provides the best effect in lowering BP, increasing arterial elasticity and thus reducing the risk of CVD. [5] In this regard, guidelines from the American College of Cardiology (ACC)/American Heart Association (AHA), International Society of Hypertension (ISH) or the European Society of Cardiology (ESC)/European Society of Hypertension (ESH) recommend that individuals with hypertension should perform at least 30 min of dynamic aerobic exercise (walking, jogging, cycling or swimming) at a moderate intensity ve to seven days per week, as well as resistance exercise two to three days per week.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, as a consequence of insufficient physical activity (PA) and an inappropriate way of life represents one of the quickest growing trends among the elderly population. As a result, physical exercise (PE) is recommended as one of the most effective means of solving the aforementioned problem (Han, Tajar, & Lean, 2011;Petrović & Marinković, 2018), as it also contributes to the improvement in quality of life, increase in muscle strength, and endurance (Blair, LaMonte, & Nichaman, 2004). In addition to numerous recommendations regarding the frequency and intensity of the physical activities of the elderly, the effects of the applied exercises, due to great variations in the aging process, according to certain authors, primarily depend on the health status, psychophysical characteristics and functional abilities of each individual (Taylor et al, 2004).…”
Section: Introductionmentioning
confidence: 99%